b) 4. (x-4)-6. (2–2x) = 4 . (2x-6)
equação de primeiro grau
Soluções para a tarefa
Respondido por
1
Resposta:
x = -1/4 ou x = -0,25
Explicação passo-a-passo:
4 * (x-4) - 6 * (2–2x) = 4 * (2x-6)
4x - 16 - 12 - 12x = 8x - 24
4x - 12x - 16 -12 = 8x - 24
-8x - 28 = 8x - 24
-8x - 8x = -24 + 28
-16x = +4 * (-1)
16x = -4
x = -4/16
x = -1/4 ou x = -0,25
Perguntas interessantes
Matemática,
8 meses atrás
Inglês,
9 meses atrás
Matemática,
9 meses atrás
ENEM,
1 ano atrás
ENEM,
1 ano atrás
Português,
1 ano atrás